2007
DOI: 10.1186/1477-7819-5-73
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes for colon and rectal cancer over a decade: results from a consecutive monocentric experience in 902 unselected patients

Abstract: A prospective, uniform follow-up policy used in a single institution over the last decade provides evidence of quality assurance in colorectal cancer surgery with high rates of resection for cure where only stage at presentation functions as an independent variable for cancer-related outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
45
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 29 publications
9
45
1
2
Order By: Relevance
“…Andreoni et al (3) reported no statistical difference between those groups (37.5% vs 41.1%, P = 0.44), although extended resections required more blood transfusions (16.3% vs 10%, P = 0.03).…”
Section: Discussionmentioning
confidence: 97%
“…Andreoni et al (3) reported no statistical difference between those groups (37.5% vs 41.1%, P = 0.44), although extended resections required more blood transfusions (16.3% vs 10%, P = 0.03).…”
Section: Discussionmentioning
confidence: 97%
“…Recurrence in rectal carcinoma is scarcely tolerable for patients because there is a higher risk of permanent stoma that may lead to pelvic exenteration and increased morbidity in patients because of deep pelvic abscess, delay in perineum healing and leakage (Wiig et al, 2007;Ferenschild et al, 2009). Andreoni et al (2007) showed that recurrence in rectal cancer is significantly higher than with colon cancer (14% versus 6.1%; p<000.1). In addition, a study by Li M et al (2008) demonstrated that the recurrence of rectal cancer is 1.5 times higher than colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In our patients, local recurrences were seen in 11.2% following RC Local recurrence after the resection of colon cancer was 28% vs. 18% in the Barcelona trial [34]. In our study local recurrence following open surgery (10.2%) was lower than Barcelona trial.…”
Section: Oncological Outcomementioning
confidence: 46%
“…In a meta-analysis of 13 trials operating time in laparoscopy was longer (p=0.027) in all but one (32) study. In addition, most of the studies have observed significantly lower mean blood loss following the laparoscopic approach [34]. Though our blood losses in both groups were higher (689 ml vs. 323 ml) laparoscopy group had a lower blood loss).…”
Section: Open Surgery Vs Laparoscopymentioning
confidence: 49%